2022
DOI: 10.3390/app12052318
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Fuzzy Logic on MPPT and PI Controllers in the Chain of Photovoltaic Control Systems

Abstract: This paper presents a comparative study between two maximum power point tracking (MPPT) algorithms, the incremental conductance algorithm (InC) and the fuzzy logic controller (FLC). The two algorithms were applied to a low photovoltaic power conversion system, and they both use different PI controllers and grid synchronization techniques. Moreover, both InC and FLC methods have Clarke and Park Transformation. To some extent, the incremental conductance and fuzzy logic controller approaches are similar, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…For the control and optimization of the photovoltaic system, the fuzzy control algorithm and neural network control algorithm have been widely studied and applied in recent years. Giurgi et al [36] found that the fuzzy control algorithm can effectively improve the power generation efficiency of photovoltaic system under certain lighting and temperature conditions, but in some cases, there were also cases of power output reduction. This is consistent with the conclusion of this study, which shows that the fuzzy control algorithm has a certain universality in different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For the control and optimization of the photovoltaic system, the fuzzy control algorithm and neural network control algorithm have been widely studied and applied in recent years. Giurgi et al [36] found that the fuzzy control algorithm can effectively improve the power generation efficiency of photovoltaic system under certain lighting and temperature conditions, but in some cases, there were also cases of power output reduction. This is consistent with the conclusion of this study, which shows that the fuzzy control algorithm has a certain universality in different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Once this condition is satisfied, that point is called the maximum power point denoted as (MPP). To extract this MPP out of the module it will be essential to drive the current operating point to operate at the peak level of the MPP of the P-V curve [34], [35].…”
Section: Introductionmentioning
confidence: 99%
“…Based on that, the researchers focused on proposing different algorithms to guarantee accurate and fast tracking to the Maximum Power Point (MPP). Regardless of the type of PV system, whether it is a standalone or grid-connected system, guaranteeing MPP tracking condition maximizes the level of harvested energy from the incident sunlight [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The proposed algorithms have different characteristics, including both pros and cons, in terms of response speed, tracking accuracy, and oscillation at steady state conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Fuzzy Logic Control (FLC) is introduced for MPP tracking function to overcome the mentioned disadvantages of P&O and IC through a quick and stable response using fuzzification, Fuzzy rules, and defuzzification processes [11][12][13][14]. A new global MPP tracker combined FLC and an algorithm of scanning and storing process presented in [15] for stand-alone PV systems that work under partially shaded weather conditions.…”
Section: Introductionmentioning
confidence: 99%